DINAMIKA KEBIJAKAN PENGENDALIAN KONVERSI LAHAN PERTANIAN DI KOTA SUKABUMI - Basori, Yana Fajar FY. (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2016)
Local Government of Sukabumi City face a dilemma situation in relation to agricultural land conversion. On the one hand, local governments are obliged to accelerate the pace of economic growth through the development of industrial sectors, services, and property. But on the other hand, local governments should also give attention to efforts to defend and protect the existence of farm lands for the preservation of agricultural production. Formulation and implementation of land policy is needed to allow the system to continue business. Has not seen any technological breakthrough or Local Government efforts to compensate for the decline in agricultural production caused by loss of land. Local Government has proposed an alternative policy to restrict or prevent the conversion of fertile farmland into land as non-agricultural land policies that take into account the allocation of land use as well as the establishment of a sustainable land. Determination of the policy in the form of Regional Regulation is necessary to comprehensively wetland protection strategy based on the dynamics of policy-setting sustainable agricultural land. By focusing attention on the formulation and implementation of policies, indicators of a generic that can be used are: (1) the quality of the substance of the policy that contains guarantee people's basic rights, (2) the quality of the process of formulation and implementation of policies that contain respect for the principle of citizenship and democratic governance good and right. Both of these approaches is sufficient to be value inherent in the management of the dynamics of land conversion control policy related socio-agrarian identification, mapping the agrarian structure and relationship patterns that occur on the possession, control, utilization and land use policy into a whole discussion dynamics.